The Austrian Vice-Chancellor (middle) reviewing detachments of the Militia during his visit to Rome to discuss the continuation of Austro-Italian co-operation. From: Keesings Wereldgebeuren in Beeld, nr.728
The Austrian Vice-Chancellor (middle) reviewing detachments of the Militia during his visit to Rome to discuss the continuation of Austro-Italian co-operation. From: Keesings Wereldgebeuren in Beeld, nr.728.